The Influence of Teacher Role Models on the Learning Manners of Students at Islamic Boarding Schools - Alwi, Nailis Sa’adah; Zaitun, Zaitun; Idris, Idris (STIT Ahlussunnah Bukittinggi, 2025)
Discussions about santri etiquette are always interesting to study because they are directly related to every action and behavior of santri that is in line with the character values in educational goals. This study aims to examine the influence of teacher role modeling and self-regulated learning on santri learning etiquette at the Darussalam Islamic Boarding School in Kabun. This study uses a quantitative approach with a correlation method. Data collection techniques include questionnaires, observations, and documentation. Data analysis techniques to measure all variables in this study use SPSS version 24 software, starting with preliminary data tests consisting of normality tests and linearity tests, followed by hypothesis testing, specifically simple regression tests. The sample consisted of 187 students selected from a total population of 350 male and female students at the Darussalam Islamic Boarding School in Rokan Hulu, Riau. The sample was selected using the Slovin formula, and the researcher employed probability sampling techniques. The results of this study indicate that the influence of teacher role modeling on student learning manners is 28%. Thus, there is a significant influence of teacher role modeling on student learning manners at the Darussalam Islamic Boarding School in Kabun, Rokan Hulu.